2001
DOI: 10.1677/joe.0.1690333
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin A is a follicle stimulating hormone-responsive marker of granulosa cell differentiation, which has both autocrine and paracrine actions in sheep

Abstract: The aim of these studies was to examine the origin, control and local actions of inhibin A in monovular species, using the sheep as a model. Experiment 1 examined the pattern of mRNA expression for the inhibin subunits in relation to follicular size and pattern of expression to other differentiative markers in granulosa (P450 aromatase) and thecal cells (P450 17 -hydroxylase). Experiment 2 examined the pattern of inhibin A production, in relation to oestradiol, by granulosa cells induced to differentiate in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 49 publications
6
29
1
3
Order By: Relevance
“…Once again, this may have arisen, at least in part, from the increased response of granulosa cells to FSH. In vivo and in vitro studies have previously demonstrated that estradiol production by granulosa cells is FSH responsive in this species [37,38]. Estradiol is known to exert some of its actions in a paracrine manner via one of two receptors (i.e., ESR1 and ESR2), and both isoforms are expressed in sheep granulosa cells during the late preantral and antral stages of follicle development [39], coincident with the period of exposure to dietary treatments in the current study.…”
Section: Nature and Timing Of Dietary Effectssupporting
confidence: 58%
“…Once again, this may have arisen, at least in part, from the increased response of granulosa cells to FSH. In vivo and in vitro studies have previously demonstrated that estradiol production by granulosa cells is FSH responsive in this species [37,38]. Estradiol is known to exert some of its actions in a paracrine manner via one of two receptors (i.e., ESR1 and ESR2), and both isoforms are expressed in sheep granulosa cells during the late preantral and antral stages of follicle development [39], coincident with the period of exposure to dietary treatments in the current study.…”
Section: Nature and Timing Of Dietary Effectssupporting
confidence: 58%
“…Functionality of preovulatory follicles can be assessed both by direct (assessment of their growth dynamics and/or hormonal secretion) and indirect approaches (assessment of subordinate follicles for evidencing dominance effects driven by hormonal secretion of the large follicles). In sheep, E 2 and inhibin-A are considered as good markers of follicular quality (Campbell et al 1995, Campbell & Baird 2001, Gonzalez-Bulnes et al 2004c and, in the current study, both hormones were reduced in older ewes. In women, both E 2 and inhibin-A decrease during the ovarian aging process, although there is an earlier decrease in inhibin-B (Broekmans et al 2009), a hormone which is not produced by the sheep ovary (McNeilly et al 2002).…”
Section: Discussionsupporting
confidence: 57%
“…Thus in the mouse we have no evidence for production of inhibins outwith the granulosa compartment. In a recent study in the sheep using in situ hybridization, expression of all inhibin subunits was also confined to the granulosa cells (Campbell & Baird 2001).…”
Section: Discussionmentioning
confidence: 96%